2021
DOI: 10.1002/ajim.23281
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 mortality among Amalgamated Transit Union (ATU) and Transport Workers Union (TWU) workers—March–July 2020, New York City metro area

Abstract: Background Transit workers have jobs requiring close public contact for extended periods of time, placing them at increased risk for severe acute respiratory syndrome coronavirus 2 infection and more likely to have risk factors for coronavirus disease 2019 (COVID‐19)‐related complications. Collecting timely occupational data can help inform public health guidance for transit workers; however, it is difficult to collect during a public health emergency. We used nontraditional epidemiological surveillance method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…This study demonstrated that media scraping may be useful for identifying occupational safety and health outcomes outside of fatality counts ( Kelly-Reif et al, 2021 , Tomasi et al, 2021 ). Using a combination of multiple search engines, case identification was maximized and represented a strength of the study.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…This study demonstrated that media scraping may be useful for identifying occupational safety and health outcomes outside of fatality counts ( Kelly-Reif et al, 2021 , Tomasi et al, 2021 ). Using a combination of multiple search engines, case identification was maximized and represented a strength of the study.…”
Section: Discussionmentioning
confidence: 86%
“…Nearly a quarter of the WVEs involved a customer voluntarily coughing or spitting on a worker while threatening infection from SARS-CoV-2. Media reports have previously been used to surveil for COVID-19 fatalities among various occupations, but the current study suggests these methods may also be useful for other occupational safety and health outcomes, such as workplace violence ( Kelly-Reif et al, 2021 , Tomasi et al, 2021 ). In addition, the Kelly-Reif et al study found the sensitivity of media scans to detect first responder COVID-19 fatalities was high at 88% ( Kelly-Reif et al, 2021 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…, 2021). Also, data gathered through nontraditional epidemiological surveillance such as NLEOMF database may help to provide insight into risk factors and potential mitigation strategies among occupations (Tomasi et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Routine collection of data on occupation would help to improve understanding of COVID-19 deaths in first responders (Kelly-Rief et al, 2021). Also, data gathered through nontraditional epidemiological surveillance such as NLEOMF database may help to provide insight into risk factors and potential mitigation strategies among occupations (Tomasi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%